Creation of the Vehicle Technical Inspection Centre (CRTV) to Improve Service in the GADM, Riobamba, Province of Chimborazo - Alejandra Viñán Villagrán, Janneth; Andrés Uvidia Inca, Diego; Marcelo Llamuca Auquilla, Iván (ESPOCH Congresses: The Ecuadorian Journal of S.T.E.A.M., 2022)
The present research aims to ensure the minimum safety conditions of vehicles, identify mechanical failures, verify compliance with the technical regulations that regulate them, and improve road safety. This project is based on the data of the vehicle fleet and vehicle registration – the vehicles were classified by their type (light, heavy, motorcycles) and the future projection was made to determine the number of revision lines and the necessary equipment to supply it. For the subsequent implementation of the CRTV, the economic feasibility analysis was carried out through the study of the three Financial Management Models. The indicators provided the necessary tools for accurate decision-making regarding the acquisition of infrastructure and equipment, in addition to the necessary administrative and operative personnel. We obtained a net present value of $333,063.35 and an internal rate of return of 27%. In addition, the cost– benefit ratio was 1.62, which indicates economic and social benefits. Financial Management Model by concession is the most suitable for the study area because the indicators show that the performance of the project is recommended. Keywords: economic and administrative sciences, vehicle technical review, transport, occupancy rate, review line, inen technical standard, financial viability, Riobamba (canton). Resumen El presente trabajo de investigación “Creación del Centro de Revisión Técnica Vehicular (CRTV) para mejorar el servicio en el GADM-Riobamba, provincia de Chimborazo.”, tiene la finalidad de garantizar las condiciones mínimas de seguridad de los vehículos, identificar las fallas mecánicas, verificar el cumplimiento de la normativa técnica que les regula y mejorar la seguridad vial. El desarrollo del presente proyecto tomó como base los datos del parque automotor y matriculación vehicular, se clasificó para los vehículos por su tipología (livianos, pesados y motocicletas) y se realizó la proyección de la demanda insatisfecha para determinar el número de líneas de revisión y los equipos necesarios para abastecer la demanda futura. Para la posterior implementación del CRTV, se analizó económicamente la factibilidad mediante el estudio de los tres Modelos de Gestión Financiera, los indicadores proporcionaron las herramientas necesarias para una acertada toma de decisiones en lo referente al financiamiento de infraestructura y equipos, además del personal administrativo y operativo necesario. En el Modelo de Gestión Financiera por concesión se obtuvo un valor actual neto de $333.062,35 y una tasa interna de retorno del 27%; además la relación beneficio costo es de 1,62 lo que indica beneficio económico y social. Finalizada la evaluación económica, este modelo es el más adecuado para el área de estudio, porque los indicadores muestran un buen rendimiento del proyecto, por lo que se lo considera recomendable. Palabras Clave: ciencias económicas y administrativas, revisión técnica vehicular, transporte, tasa de ocupación, línea de revisión, norma técnica inen, viabilidad financiera, Riobamba (cantón).